2020
DOI: 10.2147/cmar.s244280
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Inhaled Anesthetics in Tumorigenesis and Tumor Immunity</p>

Abstract: Inhaled anesthetics are widely used for induction and maintenance of anesthesia during surgery, including isoflurane, sevoflurane, desflurane, haloflurane, nitrous oxide (N 2 O), enflurane and xenon. Nowadays, it is controversial whether inhaled anesthetics may influence the tumor progression, which urges us to describe the roles of different inhaled anesthetics in human cancers. In the review, the relationships among the diverse inhaled anesthetics and patient outcomes, immune response and cancer cell biology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The dynamic changes in PBMCs during the perioperative period differed according to the route of anaesthesia. The effect of different anaesthetics on immunity has been the focus of substantial body of anaesthesiology research 32,33 . Studies have been conducted on patients’ immune status 34–36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic changes in PBMCs during the perioperative period differed according to the route of anaesthesia. The effect of different anaesthetics on immunity has been the focus of substantial body of anaesthesiology research 32,33 . Studies have been conducted on patients’ immune status 34–36 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of different anaesthetics on immunity has been the focus of substantial body of anaesthesiology research. 32 , 33 Studies have been conducted on patients’ immune status. 34 , 35 , 36 Other investigation has explored whether anaesthesia can inhibit the immune response of patients with cancer, thereby affecting their long‐term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The study has shown that various surgical procedures may increase the chances of invasion and migration of cancer cells; hence, it promotes their ability to disseminate in that duration [ 9 ]. Hence, treatment with desflurane, isoflurane, and sevoflurane [ 10 , 11 ] plays a crucial role in reducing the tumor recurrence postsurgery. It is crucial to choose the appropriate anesthetic for the surgical process in operating a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing interest in the impact of anesthetics and cancer progression has stimulated several in vivo and in vitro studies on the relation between different kinds of anesthetics used during surgery and cancer development Brogi and Forfori J Anesth Analg Crit Care (2022) 2: 33 and progression [48,62]. Even if the evidence is conflicting, halogenated anesthetics seemed to present several pro-inflammatory and immunosuppressive effects that can have an important impact on enhancing metastasis formation [63]. Volatile anesthetic agents are implied in the upregulation of hypoxia-inducible factors [64].…”
Section: Anesthetic Agents Volatile and Intravenous Anestheticsmentioning
confidence: 99%